Accuracy of smartwatches in predicting distance running performance - Dai, J.; Chen, G.; Gu, Z.; Qi, Y.; Xu, K. (Frontiers in Sports and Active Living, 2025)
Objective: This study examined the accuracy of smartwatches in predicting running performance.